Research Of The Application Of The Fat Of The Margarine Industry In The Production Of Margarine Obtained On The Basis Of The Process Of Hydrotransesterification (Texas Journal of Multidisciplinary Studies, 2021)
Solid fats come mainly from animal fats or vegetable oils in the form of hydrogenated oil with a melting point of 36-43 by hydrogenation with hydrogen in the presence of catalysts. The following raw materials were used for the study: Nisosel-820 catalyst containing 25% nickel metal from the Netherlands, a single-use catalyst with a reduced activity of 30%; beef fat with melting point 26 ℃; cottonseed oil with a iodine content of 112% and dry hydrogen gas were obtained. The hydrogenated oil was obtained on the basis of the following technology: cottonseed oil and beef fat were first selected in a ratio of 50:50. In this experiment, we can see that 20 ℃ 29% and 38% of the 1st and 2nd samples have curves, and in general the minimum crystallization requirement is that the amount of solid triglyceride at 20 ℃ should not be less than 23%. This means that the obtained hydrotransesterification parameters satisfy the law